Standards and Guidelines for the Psychotherapies - Cameron, Paul (Paul M.); Deadman, John; Ennis, Jon (Book collections on Project MUSE., 1998)
Standards and Guidelines for the Psychotherapies provides a comprehensive overview of the art and science of psychotherapy and a set of practice guidelines for psychiatrists. The main aim is to improve standards and practices, and to initiate discussion. This book was developed from a report by the Joint Task Force on Standards and Guidelines for Medical (Psychiatric) Psychotherapy, which was established by the Ontario Psychiatric Association and Ontario Medical Association (Section of Psychiatry). The report was prepared in response to four phenomena emerging in recent psychotherapy: 1) The realization that there were no written guidelines or standards for the practice of medical psychotherapy; 2) the changing forces that now influence health policy and funding, both in U.S. and Canada; 3) The potential for arbitrary deinsurance of some procedures in the absence of agreed upon standards, and without regard to the evidence for the effectiveness of psychiatric procedures; and 4) Growing concern regarding the problem of sexual abuse of patients by physicians. This is an excellent reference book for medical professionals practicing in the field of psychotherapy, and will prove to be a valuable resource in the ongoing practice and development of psychotherapy.